Proceedings of the International Conference "Actual Issues of Mechanical Engineering" 2017 (AIME 2017) 2017
DOI: 10.2991/aime-17.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

Induction heating based on permanent magnets with magnetic field concentrators

Abstract: -To study the effect of various types of magnetic field concentrators on the energy and thermal characteristics of the induction heating system of noncylindrical billets in the magnetic field of rotating permanent magnets, a numerical model was developed. The model allows solving the conjugate electromagnetic and thermal problem. Using the model, the authors were able to calculate the integral active power released in the heated billet, the mechanical moment that the magnetic system experiences from the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…While several studies have examined the effects of eddy currents on the power loss of electro-motors, generators, and induction heating devices, few have investigated ways to capture the thermal energy created by eddy currents in F I G U R E 1 Eddy current principle renewable energy systems for heating buildings. [14][15][16] Neumeier studied different ways of generating heat based on the wind thermal systems and suggested that the PMECH in wind energy storage systems can achieve temperatures up to 560°C or 600°C. 17 Karasu provided a thermodynamic assessment of a wind thermal energy storage system based on the PMECH system incorporated into the nacelle of the wind turbines for heating the molten salt.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies have examined the effects of eddy currents on the power loss of electro-motors, generators, and induction heating devices, few have investigated ways to capture the thermal energy created by eddy currents in F I G U R E 1 Eddy current principle renewable energy systems for heating buildings. [14][15][16] Neumeier studied different ways of generating heat based on the wind thermal systems and suggested that the PMECH in wind energy storage systems can achieve temperatures up to 560°C or 600°C. 17 Karasu provided a thermodynamic assessment of a wind thermal energy storage system based on the PMECH system incorporated into the nacelle of the wind turbines for heating the molten salt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While several studies have examined the effects of eddy currents on the power loss of electro‐motors, generators, and induction heating devices, few have investigated ways to capture the thermal energy created by eddy currents in renewable energy systems for heating buildings 14–16 . Neumeier studied different ways of generating heat based on the wind thermal systems and suggested that the PMECH in wind energy storage systems can achieve temperatures up to 560°C or 600°C 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, permanent magnet devices contribute to increase in efficiency (from 50% to more than 70%) allowing not only to reduce the cost of energy used but also leading to positive on environment, as demonstrated in [6]. The real problem are always the magnets demagnetization risks at high temperatures [6][7][8][9], in this case, contrary to magnetic refrigeration systems, permanent magnets must be thermally insulated. Refrigeration with the use of permanents magnets of materials has been largely used for the last ten years [10], but the competitiveness seems in favor of superconductor materials because of their strong magnetic fields, permitting large cooling power applications [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Quite a lot of papers (Aliferov et al , 2017; Bucenieks et al , 2005; Bojarevics and Beinerts, 2010; Mach et al , 2012) are devoted to the study of electromagnetic processes in cylindrical metal blanks when they are heated by means of permanent magnets, but the interaction of the magnetic field of the moving magnets with the molten metal has not been studied enough.…”
Section: Introductionmentioning
confidence: 99%